Pharmacognostic authentication and bioactivity of polyherbal essential oils from red ginger, turmeric, and aromatic ginger - ALWANI HAMAD; RETNO WAHYUNINGRUM; DIANA HASRI PUSPARINI; DINDA FARIDAENI; ELVIA MITA ISABILA; DWI HARTANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hamad A, Wahyuningrum R, Pusparini DH, Faridaeni D, Isabila EM, Hartanti D. 2025. Pharmacognostic authentication and bioactivity of polyherbal essential oils from red ginger, turmeric, and aromatic ginger. Biodiversitas 26: 5132-5144. People in Baturraden, Indonesia, use rhizomes of red ginger (Zingiber officinale var. rubrum), turmeric (Curcuma longa), and aromatic ginger (Kaempferia galanga) to make polyherbal formulations for managing masuk angin symptoms. This study aimed to verify the identity of the crude drug, determine the antioxidant properties of the formulations, and evaluate the chemical constituents and antimicrobial activity of polyherbal essential oils to assess the effectiveness for curing masuk angin symptoms. The identity of the red ginger, turmeric, and aromatic ginger crude drugs was conducted by following the pharmacopoeial method. The crude drugs were prepared into seven formulations, designated as Formula 1 through Formula 7. The antioxidant properties were evaluated using the standard 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity method, and the Total Phenolic Content (TPC) was determined using UV-Vis spectrophotometry. The antimicrobial activity was determined using the microdilution method, with the percentage of inhibition as a parameter. The polyherbal formulations exerted different DPPH scavenging activity and TPC, with the highest values observed in Formula 1[red ginger only, 178.01±3.88 mmol Trolox Equivalent (TE)/g] and Formula 2 [turmeric only, 9.60±0.28 mg Gallic Acid Equivalent (GAE)/g], respectively. Each polyherbal essential oil contained a different constituent profile. Polyherbal essential oils showed moderate antimicrobial activity against Multidrug-Resistant (MDR) Streptococcus aureus and Candida albicans, with more profound antifungal activity than antimicrobial activity. Formula 3 demonstrated the highest overall antimicrobial activity, with percentages of inhibition against Streptococcus aureus and Candida albicans were 15.75±1.32% and 71.67±3.39%, respectively. The findings confirmed the identity of the crude drugs, highlighting the potential of a local polyherbal formulation, particularly Formula 3, for its antioxidant and moderate antimicrobial activities associated with masuk angin symptoms.